2012
DOI: 10.1515/ntrev-2012-0003
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale materials for organohalide degradation via reduction pathways

Abstract: The unique chemical and physical properties of nanoscale materials have led to important roles in several scientifi c and technological fi elds. Environmental chemistry processes have benefi ted from the enhanced reactivity of nanoscale particles relative to their bulk counterparts with contaminants. Here, we describe recent advances in the synthesis and characterization of metallic and bimetallic nanoparticles that have been effective toward degrading toxic organohalide contaminants. We then review the degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Herein, we report a new, general convergent electrochemistry strategy to realize alkene alkoxyhalogenation and organohalide dehalogenation in one pot (Scheme b), which represents an electrochemistry example of alkene halofunctionalization using organohalides, including alkyl and aryl halides, as the nucleophilic halogen sources . Notable features of this method are ideal atom utilization, excellent selectivity, broad substrate scope, and no halogen ambient pollution by avoiding the release of halide ions from the carbon–halogen bond cleavage into the environment . This technology also offers efficient access to deuterated compounds by electrochemical dehalogenation deuteration of the organohalides with deuterated alcohols …”
mentioning
confidence: 99%
“…Herein, we report a new, general convergent electrochemistry strategy to realize alkene alkoxyhalogenation and organohalide dehalogenation in one pot (Scheme b), which represents an electrochemistry example of alkene halofunctionalization using organohalides, including alkyl and aryl halides, as the nucleophilic halogen sources . Notable features of this method are ideal atom utilization, excellent selectivity, broad substrate scope, and no halogen ambient pollution by avoiding the release of halide ions from the carbon–halogen bond cleavage into the environment . This technology also offers efficient access to deuterated compounds by electrochemical dehalogenation deuteration of the organohalides with deuterated alcohols …”
mentioning
confidence: 99%
“…[33][34][35][36] PET reactions are suitable for detecting CHCs due to the facile decomposition of organohalides in PET reactions due to the excellent electronaccepting behavior of halo-carbon bonds (CÀ X). [37,38] In a study by Lee et al in 2018, it was demonstrated that compounds based on triphenylamine can serve as fluorescence sensors for chloroform and chlorinated solvents using photoinduced electron transfer.c Here, we introduce a green procedure based on a low-cost derivative of phenothiazine (PTZ) and light irradiation. Phenothiazine derivatives are extensively utilized as photocatalysts in various photochemical reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, CHCs can be detected using photoinduced electron transfer (PET) phenomena, which has been used in molecular sensors [33–36] . PET reactions are suitable for detecting CHCs due to the facile decomposition of organohalides in PET reactions due to the excellent electron‐accepting behavior of halo‐carbon bonds (C−X) [37,38] . In a study by Lee et al.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] PET reactions are suitable for detecting CHCs due to the facile decomposition of organohalides in PET reactions due to the excellent electron-accepting behaviour of halo-carbon bonds (C-X). 37,38 In 2018, lee etal., have shown that compounds based on triphenylamine can work as fluorescence sensors for chloroform and chlorinated solvents through photoinduced electron transfer. 36 In this study, we present a green procedure based on a low cost phenothiazine simple derivative (PTZ) and light irradiation.…”
Section: Introductionmentioning
confidence: 99%